profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

3.Упростить выражение: а) - 0,1х(2х^2+6)(5-4x^2)

  1. Ответ
    Ответ дан Давыдова Галина
    а) - 0 , 1 * х * (2 * х ^ 2 + 6 ) * ( 5 - 4 * x ^ 2 ) = - 0 , 1 * х * (2 * х ^ 2 * 5 - 2 * x ^ 2 * 4 * x ^ 2 + 6 * 5 - 6 * 4 * x ^ 2 ) = - 0 , 1 * х * (10 * х ^ 2 - 8 * x ^ ( 2 +2) + 30 - 24 * x ^ 2 ) = - 0 , 1 * х * (10 * х ^ 2 - 8 * x ^ 4 + 30 - 24 * x ^ 2 ) = - 0 , 1 * х * ( - 8 * x ^ 4 - 14 * x ^ 2 +30) = 0 , 1 * х * 8 * x ^ 4 + 0 . 1 * 14 * x ^ 2 - 0 . 1 * 30 = 0 , 1 * х * 8 * x ^ 4 + 0 . 1 * x* 14 * x ^ 2 - 0 . 1 * x * 30 = 0 , 8 * x ^ 5 + 1 . 4 * x ^ 3 - 3 * х = х * (0 , 8 * x ^ 4 + 1 . 4 * x ^ 2 - 3);
    0